Activators of the 26S proteasome when protein degradation increases - Donghoon Lee (Experimental and Molecular Medicine)
Abstract In response to extra- and intracellular stimuli that constantly challenge and disturb the proteome, cells rapidly change their proteolytic capacity to maintain proteostasis. Failure of such efforts often becomes a major cause of diseases or is associated with exacerbation. Increase in protein breakdown occurs at multiple steps in the ubiquitin-proteasome system, and the regulation of ubiquitination has been extensively studied. However, the activities of the 26S proteasome are also stimulated, especially under highly catabolic conditions such as those associated with atrophying skeletal muscle, proteotoxic stress such as heat shock and arsenite, or hormonal cues such as cAMP or cGMP agonists. Among the proteins that enhance proteasomal degradation are the PKA, PKG, UBL-UBA proteins and the Zn finger AN1-type domain (ZFAND) family proteins. ZFAND proteins are of particular interest because of their inducible expression in response to various stimuli and their abilities to control protein quality by stimulating the 26S proteasome and p97/VCP. The regulatory roles of ZFAND proteins appear to be important not only for the control of protein degradation but also for other cellular processes, such as mRNA stability and signaling pathways. This review summarizes the known functions of proteasome activators and discusses their possible roles in regulating proteostasis and other cellular processes.